Potential mechanism underlying the effect of matrine on COVID-19 patients revealed through network pharmacological approaches and molecular docking analysis. (2nd January 2023) - Peng, Wenpan; Xu, Yong; Han, Di; Feng, Fanchao; Wang, Zhichao; Gu, Cheng; Zhou, Xianmei; Wu, Qi
Abstract: Background: The clinical efficacy of matrine in treating coronavirus disease (COVID-19) has been confirmed; however, its underlying mechanism of action remains unknown. Methods: TCMSP, SwissTargetPrediction, SEA, GeneCards, CTD, and TTD were used to identify potential targets for matrine in SARS-CoV-2. Cytoscape software was used to determine the target-pathway network for topographical analysis. The online STRING analysis platform and Cytoscape were together used to generate a PPI network and for GO and KEGG pathway enrichment analysis. Finally, molecular docking simulations were performed to study matrine-Mpro, matrine-ACE2, and matrine-RdRp interactions. Results: Ten common matrine targets were obtained, particularly including TNF-α, IL-6, and CASP3. GO and KEGG pathway enrichment analysis revealed five significantly enriched signalling pathways involved in cell proliferation, apoptosis, programmed cell death, and immune responses. Conclusions: During COVID-19 treatment, matrine regulates viral replication, host cell apoptosis, and inflammation by targeting the TNF-α, IL-6, and CASP3 in the TNF signalling pathway.